Fire & flood - Scott, Victoria (Young adult author) (Scholastic Press, 2014)
Tella's brother Cody is sick and getting worse, so when she finds instructions on how to become a contender in the dangerous Brimstone Bleed race where she can win a cure for him, she jumps at the chance--but there is no guarantee that she will win, or even survive.